Electroceuticals : Advances in Electrostimulation Therapies - Majid, Arshad (Springer International Publishing : Imprint: Springer, 2017)
This book covers recent advances in the use of electrostimulation therapies in movement disorders, epilepsy, inflammatory bowel disease, memory and cognition, disorders of consciousness, foot drop, dysphagia, brain injury, headache, heart failure, hearing loss, and rheumatoid arthritis. It describes techniques such as vagus nerve stimulation, deep brain stimulation, and electrical stimulation of the pharyngeal nerve. Electroceuticals: Advances in Electrostimulation Therapies is aimed at clinicians and basic researchers in the fields of neurology, neurosurgery, cardiology and rheumatology.
Keywords: Medicine.; Cardiology.; Rheumatology.; Neurology.; Neurosurgery.; elektronické knihy; electronic books